Stability of African swine fever virus on spiked spray‐dried porcine plasma. Issue 5 (25th June 2021) - Fischer, Melina; Pikalo, Jutta; Beer, Martin; Blome, Sandra
Abstract: African swine fever (ASF) is a viral disease that affects members of the Suidae family. The notifiable disease is considered a major threat to the pig industry, animal health, and food security worldwide. According to the European Food Safety Authority, ASF virus (ASFV) survival and transmission in feed and feed materials is a major research gap. Against this background, the objective of this study was to determine the survival of ASFV on spiked spray‐dried porcine plasma (SDPP) when stored at two different temperatures. To this means, commercial SDPP granules were contaminated with high titers of ASFV in a worst‐case external contamination scenario. Three samples per time point and temperature condition were subjected to blind passaging on macrophage cultures and subsequent haemadsorption test to determine residual infectivity. In addition, viral genome was detected by real‐time PCR. The results indicate that heavily contaminated SDPP stored at 4°C remains infectious for at least 5 weeks. In contrast, spiked SDPP stored at room temperature displayed a distinct ASFV titer reduction after 1 week (>2.8 log levels) and complete inactivation after 2 weeks (>5.7 log levels). In conclusion, the residual risk of ASFV transmission through externally contaminated SDPP is low if SDPP is stored at room temperature (21 ± 2°C) for a period of at least 2 weeks before feeding.